2010
DOI: 10.1074/jbc.m110.145110
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Interface Determines the Recognition of RNA Polymerase II by RNA Capping Enzyme*

Abstract: RNA capping enzyme (CE) is recruited specifically to RNA polymerase II (Pol II) transcription sites to facilitate cotranscriptional 5-capping of pre-mRNA and other Pol II transcripts. The current model to explain this specific recruitment of CE to Pol II as opposed to Pol I and Pol III rests on the interaction between CE and the phosphorylated C-terminal domain (CTD) of Pol II largest subunit Rpb1 and more specifically between the CE nucleotidyltransferase domain and the phosphorylated CTD. Through biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 72 publications
3
40
0
Order By: Relevance
“…In S. cerevisiae, Ser5 phosphorylation occurs first in the CTD in coordination with the recruitment of Ceg1 (47), which binds the foot of RNA pol II in S. cerevisiae (14). In agreement, we demonstrated that the foot is in contact with proteins that participate in transcription initiation and/or early elongation (13) and that interact genetically with CEG1.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…In S. cerevisiae, Ser5 phosphorylation occurs first in the CTD in coordination with the recruitment of Ceg1 (47), which binds the foot of RNA pol II in S. cerevisiae (14). In agreement, we demonstrated that the foot is in contact with proteins that participate in transcription initiation and/or early elongation (13) and that interact genetically with CEG1.…”
Section: Resultssupporting
confidence: 66%
“…Suh et al have reported previously that mutating the foot domain significantly reduced the amount of CE associated with RNA pol II in S. cerevisiae (14). Thus, if the impairment of the Ceg1 interaction with RNA pol II is responsible for the slowgrowth phenotypes of the rpo21-4 and rpb1-84 mutants, overexpression of CEG1 might compensate for these phenotypes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations